Electron ionization mass spectra of some fused pyrimidinone derivatives - Mäki Esa (RAPID COMMUNICATIONS IN MASS SPECTROMETRY, 1994)
The electron ionization mass spectra of 19 tricyclic fused pyrimidinone derivatives were studied. The molecular ions of almost all of these compounds were very stable and formed the base peaks of the spectra. The degree of saturation, the size and substitution of rings A and C (pyrimidinone itself is ring B) were the dominant factors affecting the type of fragmentation which, however, in general was quite simple.